The effect of in vitro mycorrhization on growth characteristics, changes in endogenous hormones and performance of microplants in potato (Solanum tuberosum L.) - Khosro PARVIZI; Farshad DASHTI (Journal of Central European Agriculture, 2015)
Potato (Solanum tuberosum L.) plantlets were inoculated in vitro with an arbuscular mycorrhizal fungus (Glomus intraradices) and their growth response, performance and endogenous hormonal status evaluated. A factorial experiment based on a completely randomized design consisting of two potato cultivars (Agria and Sante) and four culture media was conducted with four replications. The culture media included non-inoculated Murashige and Skoog (MS) medium (control), inoculated MS medium, inoculated half-strength MS medium and inoculated MS medium without vitamins and sugar. To do inoculation, germinated spores of fungus were transferred to the root zone of plantlets. Colonization percentage, total chlorophyll content, internodes and stolon length, shoot diameter, shoot and root fresh and dry weight, leaf area and the level of three endogenous hormones (total auxins, gibberellins and cytokinins) were determined. In addition, mini-tuber production was assayed quantitatively and qualitatively. Results demonstrated that the effect of two factors on all characteristics including mini-tuber production was different significantly. Interaction between cultivar and inoculation systems was significantly associated with endogen auxins as well as all range of mini-tuber production. The inoculated MS medium showed the better results, but it did not have significant difference to half-strength MS in terms of plantlet performance and growing parameters. Responses of both cultivars to inoculation were very conspicuous in the production of endogen hormones. Higher endogen hormone levels were associated with elevated growth parameters, greater biomass production and better plantlet performance.